ANALISIS YURIDIS PRINSIP KETERBUKAAN INFORMASI (FULL DISCLOSURE) PADA PROSES INITIAL PUBLIC OFFERING(IPO) PT.GARUDA INDONESIA (PERSERO) Tbk TERKAIT PRINSIP GOOD CORPORATE GOVERNANCE (GCG) - SARAH CASCARINA S. (PREMISE LAW JURNAL, 2015)
PT.Garuda Indonesia (Persero) Tbk has obtained the approval to do Initial Public Offering (IPO) according to the approval for privatization from the House of Representatives which is stipulated in the Letter of The Chairperson of the Indonesian House of Representatives No.PW.o1/5972/DPR RI/IX/2009 on September 16, 2009. The result of the research showed that the mechanism of IPO of PT.Garuda Indonesia (Persero) Tbk was done in three stages; preparation, registration to Bapepam LK and recording. The implementation of the principal of full disclosure is an obligatory for bankers, emission guarantor, and the other stakeholders. From judicial point of view, the principle of full disclosure is the guarantee for aspiring investors to keep people’s trust on capital market, to create the effisient mechanism of market an to forestall deception. In its development, the first day of listing the stocks in the Indonesia Stock Exchanges after doing IPO, the stocks of PT.Garuda Indonesia (Persero) Tbk decreased from Rp.750 per stock to Rp.620 per stock ordecreased 17.33 %. Since the Initial Public Offering from 2011 to 2014, the stock price has decreased and never increased above the level of IPO. Keywords: Stock, Principle of Disclosure, Initial Public Offering, Principle of Good Governance